Performances of coupled the partition of unity finite element method and the discrete shear gap method for the analysis of 3D vibro-acoustic problems. (November 2022) - Ma, Houbiao; Zhang, Yahui
Abstract: In 3D vibro-acoustic analysis, the accuracy of the vibro-acoustic FE model degrades with increasing excitation frequency due to the "dispersion error". In this paper, an efficient hybrid method, namely the PUFEM/DSG, is proposed for improving the computational performance of vibro-acoustic analysis, which uses the partition of unity finite element method for the acoustic cavity and the discrete shear gap method for the flexible shell. The acoustic cavity is discretized into tetrahedral elements of large size, and a plane wave function is introduced in the interpolation space to construct the PUFEM. Triangular elements are adopted for the shell, and the DSG eliminates the "shear locking". At the interface with non-matching meshes, this paper realizes the coupling of two field variables by dividing virtual elements and implementing coordinate transformation and applies the exact integration method for the PUFEM system matrix and coupling matrix to improve the efficiency of the proposed method. The proposed method not only retains the FEM's ability to model complex vibro-acoustic systems but also effectively reduces the "dispersion error" and the computational effort. It also can improve the accuracy by adding plane waves at the nodes of the acoustic cavity without remeshing. Highlights: A hybrid method PUFEM/DSG is proposed for improving the computational performance of 3D vibro-acoustic analysis. The efficient coupling of non-matching meshes is realized by dividing virtual elements, implementing coordinate transformation, and applying the exact integration method. The proposed method inherits the simplicity and good adaptability of the FEM/FEM and has better accuracy, efficiency, and convergence.